ANALYSIS OF CONTRACT AGREEMENTS THROUGH VERBAL AND ITS CONSEQUENCES ON WAGES ACCORDING TO THE THEORY OF IJARAH AL-‘AMAL: A Case Study at a Brick Factory in Gampong Miruek Taman, Aceh Besar, Indonesia - Sariyul Fatan; Riadhus Sholihin (Al-Mudharabah: Jurnal Ekonomi dan Keuangan Syariah, 2026)
This study examines the validity of employment agreements based on verbal agreements from the perspective of ijarah al- ‘amal, a form of employment contract in Islamic law. In the informal sector, employment relationships are often established verbally, based on trust and community customs, even though this raises legal issues regarding the proof and clarity of the parties’ rights and obligations. This study uses a normative juridical method, with a conceptual approach, drawing on a review of classical and contemporary fiqh literature, the Qur’an, hadith, and labour laws and regulations. The results of the study show that Islam permits verbal employment agreements provided the contract meets the following conditions: the existence of the contracting parties, a clear object of work, a known reward, and the willingness of both parties. However, verbal agreements that contain elements of gharar (uncertainty) or zulm (injustice) may render the contract invalid under both moral and legal principles. The hadith of the Prophet Muhammad SAW, which prohibits sales and purchases that contain gharar, emphasises the importance of clarity in every contract. In the contemporary context, although verbal agreements remain valid under the principle of ijarah al-'amal, written records are highly recommended to prevent disputes and protect workers’ rights. Thus, the concept of ijarah al-'amal provides legal legitimacy to verbal agreements and emphasises the importance of justice, trustworthiness, and transparency in modern employment relationships.